2008
DOI: 10.1002/ajmg.c.30168
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of obsessive compulsive disorder: A review of the evidence

Abstract: Obsessive compulsive disorder (OCD) is a common psychiatric disorder that can have disabling effects on both adults and children. Twin, family, segregation, and linkage studies have demonstrated that OCD is familial, that the familiality is due in part to genetic factors and there are regions of the genome which very likely harbor susceptibility loci for OCD. Over 60 candidate gene studies have been conducted. Most studies have focused on genes in the serotonergic and dopaminergic pathways. Unfortunately, none… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
136
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 67 publications
5
136
0
7
Order By: Relevance
“…A number of twin (van Grootheest et al, 2005) and family (Black et al, 1992;Do RosarioCampos et al, 2005;Hanna et al, 2005;van Grootheest et al, 2005;Nicolini et al, 2009;Pauls, 2010) studies indicate that genetic factors contribute to its aetiology. The environment has also been found to play a role in the development of the disorder e twin studies indicate that approximately 50% of individual variation in OCD is due to nongenetic, environmental factors (Samuels, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A number of twin (van Grootheest et al, 2005) and family (Black et al, 1992;Do RosarioCampos et al, 2005;Hanna et al, 2005;van Grootheest et al, 2005;Nicolini et al, 2009;Pauls, 2010) studies indicate that genetic factors contribute to its aetiology. The environment has also been found to play a role in the development of the disorder e twin studies indicate that approximately 50% of individual variation in OCD is due to nongenetic, environmental factors (Samuels, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…114 Although the etiology of OCD remains unknown, the results of twin studies, familial studies, and segregation analysis have provided evidence that OCD has a strong genetic component. [115][116][117][118][119] Some investigators have also found markers of oxidative stress in the brain tissues of patients with OCD. [120][121][122] Moreover, Kuloglu et al 120 showed significantly lower levels of vitamin E and C, and higher levels of malondialdehyde (MDA) in patients with OCD compared to controls, suggesting that OCD is linked to oxidative stress.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%
“…Like other psychiatric disorders, such as schizophrenia or bipolar disorder, OCD is etiologically heterogeneous, involving contributions of both genetic and environmental factors (Geller & March, 2012;Koran & Blair Simpson, 2013;Pauls, 2008;Stewart & Pauls, 2010). Heritability estimates for childhood onset OCD range from 45% to 65% (van Grootheest, Cath, Beekman, & Boomsma, 2005).…”
Section: Introductionmentioning
confidence: 99%